2014
DOI: 10.1371/journal.pone.0098031
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Inulin and Its Role in the Prevention of Human Colonic Muscle Cell Impairment Induced by Lipopolysaccharide Mucosal Exposure

Abstract: BackgroundFructans, such as inulin, are dietary fibers which stimulate gastro-intestinal (GI) function acting as prebiotics. Lipopolysaccharide (LPS) impairs GI motility, through production of reactive oxygen species. The antioxidant activity of various fructans was tested and the protective effect of inulin on colonic smooth muscle cell (SMC) impairment, induced by exposure of human mucosa to LPS, was assessed in an ex vivo experimental model.MethodsThe antioxidant capacity of fructans was measured in an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 47 publications
(49 reference statements)
2
55
0
Order By: Relevance
“…Inulin increases absorption of vitamins and minerals; especially calcium and magnesium, protects body from translocation of bacteria and proliferation of pathogens, regulates intestinal epithelial cell growth, contributes to immune functions, and reduces triglycedaemia in hyperlipidaemic and hyperinsulemia individuals [80]. Inulin protected the mucosal and submucosal membranes against protein oxidation, reducing the oxidative stress, by protecting colon from lipopolysaccharides (LPS)-induced damage [81]. LPS are produced by gram-negative bacteria that impair intestinal smooth muscle contractibility, and increase inflammation [81].…”
Section: Soluble Fiber; Inulin Role In Cancer Development Mechanism mentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin increases absorption of vitamins and minerals; especially calcium and magnesium, protects body from translocation of bacteria and proliferation of pathogens, regulates intestinal epithelial cell growth, contributes to immune functions, and reduces triglycedaemia in hyperlipidaemic and hyperinsulemia individuals [80]. Inulin protected the mucosal and submucosal membranes against protein oxidation, reducing the oxidative stress, by protecting colon from lipopolysaccharides (LPS)-induced damage [81]. LPS are produced by gram-negative bacteria that impair intestinal smooth muscle contractibility, and increase inflammation [81].…”
Section: Soluble Fiber; Inulin Role In Cancer Development Mechanism mentioning
confidence: 99%
“…Inulin protected the mucosal and submucosal membranes against protein oxidation, reducing the oxidative stress, by protecting colon from lipopolysaccharides (LPS)-induced damage [81]. LPS are produced by gram-negative bacteria that impair intestinal smooth muscle contractibility, and increase inflammation [81]. It has been hypothesized that hyperinsulemia could be a key factor in tumor development, Inulin by decreasing serum glucose could inhibit tumor growth; moreover, the prebiotic bacteria growth complements the lactic acid, which is shown to have antigenotoxic and anticarcinogenic properties [11] [82].…”
Section: Soluble Fiber; Inulin Role In Cancer Development Mechanism mentioning
confidence: 99%
“…Additionally, several studies have convincingly shown [56] suggesting that they may play an antioxidant role in vivo. Interestingly, in a recent study, the potential protective effect of inulin, to alleviate LPS induced oxidative stress was reported [57]. This evidence indicates that the protective effect of prebiotics may be at least in part mediated by antioxidative mechanism/s.…”
Section: Discussionmentioning
confidence: 95%
“…This allows the prebiotic to reach the colon intact and undergo fermentation by a limited number of bacteria genera/species. Interestingly, we have recently demonstrated that inulin preserves its antioxidant capability following cooking and simulated digestion processes [2]. …”
Section: Introductionmentioning
confidence: 99%